Numerical and Physical Investigation of the Mixing Process in Gas Stirred Ladle System - Lakkum, Sathaporn; Ninpetch, Patiparn; Phophichit, Nadnapang; Kowitwarangkul, Pruet; Tawai, Atthasit; Otarawanna, Somboon (Applied Science and Engineering Progress, 2021)
Secondary steelmaking or ladle metallurgy is one of the important processes that adjust and homogenize the chemical compositions and the temperature. In this process, argon gas is injected into the melt through porous plugs to accelerate the chemical reaction and the mixing. One of the indicators for the mixing efficiency is “the mixing time”. The purposes of this study were to investigate the effects of gas flow rate and purging system on the mixing time and flow characteristics by using numerical and physical investigation and to predict the velocity magnitude acting on the refractory wall by analyzing the effects of gas flow rate. A 1:5 scaled water model and a full-scale ladle model of Millcon steel PLC were used in the study. The numerical simulation modelling was carried out by using CFD commercial software Flow-3D. The results from the numerical simulation were in consistence with the experiment results. The simulation results showed that with the highest gas flow rate the reduction of the mixing time was around 36% and the velocity magnitude increased to approximately 44% in comparison with the lowest gas flow rate in the full-scale model. The area at the ladle wall near the liquid surface has a higher chance of the damage than other areas. Besides, employing the dual-plugs system led to approximately 33–49% shorter mixing time compared to the single-plug system. The results show that the gas flow rate affects the turbulent kinetic energy directly. However, high turbulent kinetic energy leads to open-eye size which results in re-oxidation and contamination. Therefore, it is important to optimize the flow rate to achieve both productivity and steel cleanliness.